Book Review: Gender Ideology and Pastoral Practice. A Handbook for Catholic Clergy, Counsellors, and Ministerial Leaders (2024) - Tylka, Dominik (Chrześcijaństwo-Świat-Polityka, 2025)
The article is a review of the book “Gender Ideology and Pastoral Practice. A Handbook for Catholic Clergy, Counsellors, and Ministerial Leaders” (2024). The author summaries the main themes of the book, which addresses the identity crisis of the early 21st century. The work is divided into seven parts, covering topics such as understanding sexual identity, ideological colonisation, pastoral principles, care for transitioners and detransitioners, legal considerations, and language. The book emphasises the problem of the spread of gender ideology in societies and provides guidance on how Catholics should respond in such conditions. The author highly rates the book, noting its comprehensive approach to the complex issue of gender ideology and its impact on personal, social and political life. The book underlines the importance of Christian anthropology in understanding and addressing these challenges.